VD_FINDINFO AI 331/22 - 342/2023 vom 23. November 2023 - VD Tribunal cantonal (2023)
AIASSURANCE, NOUVELLE DEMANDE, REJET DE LA DEMANDE, DEMI-RENTE, EXPERTISE PLURIDISCIPLINAIRE | 28 LAI, 29 LAI, 4 al. 1 LAI, 16 LPGA, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA